Cloning of an apparent splice variant of the rat N-methyl-D-aspartate receptor NMDAR1 with altered sensitivity to polyamines and activators of protein kinase C. - Durand, G M (1992)
Molecular cloning identified complementary DNA species, from a rat ventral midbrain library, encoding apparent splice variants of the N-methyl-D-aspartate (NMDA) receptor NMDAR1 (which we now term NR1a). Sequencing revealed that one variant, NR1b, differs from NR1a by the presence of a 21-amino acid insert near the amino end of the N-terminal domain and by an alternate C-terminal domain in which the last 75 amino acids are replaced by an unrelated sequence of 22 amino acids. NR1b is virtually identical to NR1a in the remainder of the N- and C-terminal domains, at the 5' and 3' noncoding ends, and within the predicted transmembrane domains and extracellular and cytoplasmic loops. These findings suggest that the two forms of the receptor arise by differential splicing of a transcript from the same gene. Sequencing of other clones indicates the existence of a third variant, NR1c, identical to NR1b in its C terminus but lacking the N-terminal insert. NR1b RNA injected into Xenopus oocytes generated functional homomeric NMDA channels with electrophysiological properties distinct from those of NR1a homomeric channels. NR1b channels exhibited a lower apparent affinity for NMDA and for glutamate. NR1b channels exhibited a lower affinity for D-2-amino-5-phosphonovaleric acid and a higher affinity for Zn2+. The two receptor variants showed nearly identical affinities for glycine, Mg2+, and phencyclidine. Spermine potentiation of NMDA responses, prominent in oocytes injected with rat forebrain message, was also prominent for NR1a receptors, but was greatly reduced or absent for NR1b receptors. Treatment with the protein kinase C activator phorbol 12-myristate 13-acetate potentiated NMDA responses in NR1b-injected oocytes by about 20-fold; potentiation of NMDA responses in NR1a-injected oocytes was much less, about 4-fold. These findings support a role for alternate splicing in generating NMDA channels with different functional properties.